2018
DOI: 10.1371/journal.ppat.1007260
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of commensal fungus Wallemia mellicola in the gastrointestinal mycobiota enhances the severity of allergic airway disease in mice

Abstract: The gastrointestinal microbiota influences immune function throughout the body. The gut-lung axis refers to the concept that alterations of gut commensal microorganisms can have a distant effect on immune function in the lung. Overgrowth of intestinal Candida albicans has been previously observed to exacerbate allergic airways disease in mice, but whether subtler changes in intestinal fungal microbiota can affect allergic airways disease is less clear. In this study we have investigated the effects of the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 54 publications
1
78
0
2
Order By: Relevance
“…In summary, GLA results from complex interactions between the different microbial components of both the gut and lung microbiotas combined with local and long-reaching immune effects. All these interactions strongly suggest a major role for the GLA in respiratory diseases, as recently documented in a mice model (Skalski et al, 2018).…”
Section: Long-reaching Immune Modulation Within the Gut-lung Axissupporting
confidence: 64%
See 1 more Smart Citation
“…In summary, GLA results from complex interactions between the different microbial components of both the gut and lung microbiotas combined with local and long-reaching immune effects. All these interactions strongly suggest a major role for the GLA in respiratory diseases, as recently documented in a mice model (Skalski et al, 2018).…”
Section: Long-reaching Immune Modulation Within the Gut-lung Axissupporting
confidence: 64%
“…Nevertheless, it is still not fully deciphered, as some studies conversely found that an early colonization with Bacteroides, including B. fragilis, could be an early indicator of asthma later in life (Vael et al, 2008). Regarding fungi, gut fungal overgrowth (after antibiotic administration or a gut colonization protocol with Candida or Wallemia mellicola) increases the occurrence of asthma via IL-13 without any fungal expansion in the lungs (Noverr et al, 2005;Wheeler et al, 2016;Skalski et al, 2018). The prostaglandin E2 produced in the gut by Candida can reach the lungs and promotes lung M2 macrophage polarization and allergic airway inflammation (Kim et al, 2014).…”
Section: Chronic Respiratory Diseasesmentioning
confidence: 99%
“…In addition to antibiotic treatment, antifungal treatment induces changes to both the bacterial and fungal communities in the gut of specific pathogen-free (SPF) mice and has been shown to exacerbate type 2 allergic airway inflammation and eosinophilia in a HDM model of AAD (Wheeler et al, 2016;Li et al, 2018). Continuous supplementation with three fungal species identified in this model to be overrepresented in the gut following antifungal treatment (Aspergillus amstelodami, Wallemia mellicola [sebi], and Epicoccum nigrum) (Wheeler et al, 2016;Li et al, 2018) or with Wallemia mellicola alone following antibiotic treatment (Skalski et al, 2018) similarly increases asthma severity (Figure 3) (Wheeler et al, 2016;Skalski et al, 2018). Antifungal treatment and the introduction of dysbiotic fungal communities to SPF mice in these studies results in changes to gut bacterial communities, including depletions of bacteria from the Lactobacillaceae family Skalski et al, 2018).…”
Section: Looking Beyond Bacteria: Fungi: the Forgottenmentioning
confidence: 99%
“…Continuous supplementation with three fungal species identified in this model to be overrepresented in the gut following antifungal treatment (Aspergillus amstelodami, Wallemia mellicola [sebi], and Epicoccum nigrum) (Wheeler et al, 2016;Li et al, 2018) or with Wallemia mellicola alone following antibiotic treatment (Skalski et al, 2018) similarly increases asthma severity (Figure 3) (Wheeler et al, 2016;Skalski et al, 2018). Antifungal treatment and the introduction of dysbiotic fungal communities to SPF mice in these studies results in changes to gut bacterial communities, including depletions of bacteria from the Lactobacillaceae family Skalski et al, 2018). However, the AAD-exacerbating effects of supplementation with a dysbiotic fungal community can be recapitulated in altered Schaedler flora mice without pre-treatment with antibiotics and in the absence of substantial changes to the bacterial microbiota Skalski et al, 2018).…”
Section: Looking Beyond Bacteria: Fungi: the Forgottenmentioning
confidence: 99%
See 1 more Smart Citation